IMPLEMENTASI PENDIDIKAN AGAMA ISLAM DI LEMBAGA PENDIDIKAN ANAK USIA DINI (Kajian Penanaman Nilai-Nilai Agama Islam di TK ABA Petarukan) - Ahmad Muntakhib (Balai Penelitian dan Pengembangan Agama Semarang, 2018)
The success of Islamic Education in early childhood is often measured by the amount of memorization of daily prayers and short letters in the Qur’an. Learning methods used by teachers have not been able to fulfill the basic needs of basic characteristics of early childhood. The moral-religious aspect seems to be only a complement to the cognitive aspects, not as a spirit that underlies the achievement of cognitive aspects. This research is a qualitative research. This study aimed to explore religious and moral values and reveal the implementation of Islamic religious education in Early Childhood Education institutions. Data collection techniques were used interview, document study, observation, and Focus Group Discussion. The research data was analyzed by interactive analysis developed by Miles and Hubberman which began with data reduction, data display, and conclusion drawing or verification. The results showed that the values developed are knowing the religion adopted, doing worship, honest, helping, polite, respectful, sportive, maintaining personal hygiene and the environment, knowing religious days, and respecting or tolerance with the religion of others. Implementation of religious values through integration in the teaching and learning process, activities before and after learning activities, learning together, Parenting, and projections of home activities.